Любовь и война: роман / П. Хэган ; пер. Е. В. Погосян - Хэган Патриция (Шарм, 1998)
Экземпляры: аб. ЦБ (20200618) / Инвентарный номер: 9307 / Цена: / Сис.шифр: 84(4/8) / Авт.знак: Х 99 / ББК: 84(7Сое)